2005
DOI: 10.1046/j.1469-1809.2005.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Wilson Disease: High Prevalence in a Mountaineous Area of Crete

Abstract: SummaryWilson disease (WD) is an autosomal recessive disorder of copper metabolism. The disorder is caused by mutations in the ATP7B gene, encoding a copper transporting P-type ATPase. The worldwide incidence is in the order of 30 cases per million, with a gene frequency of 0.56% and a carrier frequency of 1 in 90. The increased number of Wilson disease patients in the island of Crete led us to study the spectrum of mutations in a small village close to the city of Heraklion, from where many patients have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…Our data showed that 8.1% of patients with idiopathic movement disorders exhibited lower serum CP and accorded with diagnostic criteria of HCMD. This percentage is obviously high compared with 1% of frequency of WD gene carrier in general population [16], which indicates that HCMD is independent of WD gene carrier frequency. To HCMD, lower serum CP is not merely a phenomenon which WD gene carrier produces, but possibly has the etiology relation.…”
Section: Discussionmentioning
confidence: 84%
“…Our data showed that 8.1% of patients with idiopathic movement disorders exhibited lower serum CP and accorded with diagnostic criteria of HCMD. This percentage is obviously high compared with 1% of frequency of WD gene carrier in general population [16], which indicates that HCMD is independent of WD gene carrier frequency. To HCMD, lower serum CP is not merely a phenomenon which WD gene carrier produces, but possibly has the etiology relation.…”
Section: Discussionmentioning
confidence: 84%
“…The authors had also noted several differences between published primer sequences and the genomic sequence currently in the National Center for Biotechnology Information (NCBI) human genome database (Table 3). Compound heterozygotes bearing three mutations in the same WD patients have been reported by Dedoussis et al 20 p.I1148T and p.G1176R cosegregated in cis in the same patient, and the other allele harbored p.Q289X. Mak et al also found four patients who carried both p.Q1142H and p.I1148T on the same allele and another mutation on the trans allele (p.A874V, p.T1178A, 2299delC, and IVS3+1G>T, respectively).…”
Section: Pathogenesis and Molecular Analysismentioning
confidence: 85%
“…25 The highest incidence reported was six out of 90 births in the island of Crete, Greece, where a founder effect was significant. 20 The discrepancies between the old figures and the more recent studies were likely due to analytical insensitivity and the under-or mis-diagnosis of WD in the past that may have occurred in patients with a typical phenotypes, or death due to unexplained liver failure. In our experience, WD is one of the most common inherited liver disorders in East Asian populations.…”
mentioning
confidence: 94%
“…Wilson's disease occurs worldwide, is caused by mutations of the ATP7B gene, on chromosome 13 and is very rare (2), particularly in Sweden (4). In Europe, it reaches its highest frequency in Mediterranean islands (5,6), probably caused by founder effects similar to the accumulation of haemochromatosis in northern Europe (1). Whether a remote consanguinity may explain the homozygosity for ATP7B H1069Q in the present case is unknown.…”
Section: Letter To the Editormentioning
confidence: 99%